A culpa das mães como antecedente do consumo - Lima, Suzana Valente Battistella (2015)
Guilt, a negative valence emotion, is object of interest of scientific literature in consumer behavior since 1990. Mothers are a group especially susceptible to this emotion, and this dissertation’s assumption is that this emotion influences their consumption decisions. The goal is to investigate whether guilt can be a consumption’s antecedent. This research was conducted by mixed methods approach, with mothers of children between 3 and 12 years old. The first phase was a qualitative exploratory study and the second were two experiments where hypotheses were tested: 1) mother’s guilt and the child’s influence on consumption decisions; 2) mother’s guilt and yielding to child’s requests; 3) mother’s guilt and consumption of superfluous goods; the last two relations are moderated by the mother’s style of consumption and the son’s pester power. The first experiment (projective technique) confirmed the three hypotheses, and the second experiment (direct questioning) confirmed the third hypothesis and it’s moderation. The different outcomes are the result of the research strategy, since the projective technique reduces de respondent’s defenses when the topic covered is subject to social norms (Fisher, 1998). The relevance of this study is bring empirical evidence that guilt is a consumption’s antecedent. It can bring insights to mothers and managers about the relation between mother’s guilt and consumption.